Bacterial Colonization of Disposable Soft Contact Lenses Is Greater during Corneal Infiltrative Events than during Asymptomatic Extended Lens Wear - Sankaridurg, Padmaja R. (American Society for Microbiology, 2000)
Microorganisms, especially gram-negative bacteria, are considered to play a role in the etiology of certain corneal infiltrative events (CIEs) observed during soft contact lens wear. This study explored the possibility of microbial colonization of soft contact lenses as a risk factor leading to CIEs. In a clinical trial conducted from March 1993 to January 1996, 330 subjects wore disposable soft contact lenses on a 6-night extended-wear and disposal schedule. During this period, 4,321 lenses (118 during CIEs; 4,203 during asymptomatic lens wear) were recovered aseptically and analyzed for microbial colonization. A greater percentage of lenses were free from microbial colonization during asymptomatic wear than during CIEs (42 versus 23%; P < 0.0001). The incidence of gram-positive bacteria, gram-negative bacteria and fungi was greater during CIEs than during asymptomatic lens wear (P < 0.05). During asymptomatic lens wear, gram-positive bacteria were isolated most frequently and were usually normal external ocular microbiota. Of the gram-positive bacteria, the incidence of Streptococcus pneumoniae was greater during CIE than during asymptomatic wear (7.6 versus 0.6%; P < 0.0001). While gram-negative bacteria were seen in few cases during asymptomatic wear, their incidence during CIE in comparison to asymptomatic wear was substantial and significant (23.7 versus 3.8%; P < 0.0001). Also, the level of colonization was high. Of CIEs, events of microbial keratitis, contact lens acute red eye, and asymptomatic infiltrative keratitis were associated with lens colonization with gram-negative bacteria or S. pneumoniae. Colonization of soft contact lenses with pathogenic bacteria, especially gram-negative bacteria and S. pneumoniae, appears to be a significant risk factor leading to CIE.